2015
DOI: 10.1089/omi.2014.0140
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Genetics Approach to Dyslipidemia in Children and Adolescents

Abstract: Elevated triglycerides (TG) or low high density lipoprotein cholesterol (HDL-C) levels are common cardiometabolic risk factors in children. From a systems genetics standpoint, Visualization of Statistical Epistasis Networks (ViSEN) is a nonparametric entropy-based method that can characterize the global structure of interacting genetic factors. We identified a novel set of connected genetic and cardiometabolic risk factors with strong and significant interaction effects on two important dyslipidemia phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Research suggests that ViSEN is more powerful than standard regression-based methods for detecting nonlinear, non-additive interaction effects. 19,26,33 Effects of single explanatory variables, which ViSEN defines as main effects, on phenotype status is calculated using Mutual Information (MI). MI, derived from information theory, quantifies the reduction in uncertainty about the distribution of one variable given an understanding of the other.…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that ViSEN is more powerful than standard regression-based methods for detecting nonlinear, non-additive interaction effects. 19,26,33 Effects of single explanatory variables, which ViSEN defines as main effects, on phenotype status is calculated using Mutual Information (MI). MI, derived from information theory, quantifies the reduction in uncertainty about the distribution of one variable given an understanding of the other.…”
Section: Methodsmentioning
confidence: 99%
“…ViSEN is a statistical program that implements the information theory metrics of MI and IG to perform network-based analyses that quantify and visualize pairwise and higherorder epistatic interactions in case control studies. Research suggests that ViSEN is more powerful than standard regression-based methods for detecting additive non-additive interaction effects [19,26,33]. ViSEN measures the effects of single explanatory variables on case/control status in terms of MI, and the strength of pairwise interaction effects on case/control status is quantified using IG.…”
Section: Visualization Of Statistical Epistasis Network (Visen)mentioning
confidence: 99%
“…ViSEN is also able to identify and quantify both additive and non-additive interactions and provide intuitive visualization of the potentially complex relationships between large numbers of variables using a network-based approach. Additionally, ViSEN has been shown to be more powerful than standard regression-based methods in detecting interaction effects, suggesting that ViSEN is a promising investigative tool that can be applied to studies of complex traits such as BDR [20,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the findings of Yılmaz et al (27), we did not find any association between the CETP rs708272 polymorphism and biochemical parameters such as triglyceride or HDL cholesterol levels in our diabetic dyslipidemia patient group. A recent study demonstrated that a CETP rs708272 gene variant is associated with low HDL cholesterol phenotype in Turkish children (28, 29). As our patient population was on lipid-lowering drugs, insulin, and oral antidiabetics, the effects of polymorphisms on lipid parameters and glucose might be masked by drug treatments.…”
Section: Introductionmentioning
confidence: 99%